Eco‐sustainable printing of cellulosic polymeric material using bio‐colorants and bio‐crosslinkers - Faisal Ahmed; Md. Reazuddin Repon; Arnob Dhar Pranta; Md. Sayed Ragib Yasar; Md. Faisal Rakib; Ishtiak Ahmed; Toufiq Ahmed Emon; Tarakul Alam Nishat (SPE Polymers)
Abstract A sustainable solution to lessen environmental damage, improve health and fulfill the increasing need for environmentally conscious goods might be for the textile industry to use eco‐friendly printing techniques and natural colors. Without the use of toxic metal‐based mordants, this research work set out to examine how natural thickeners, biomordants, and dyes interacted when printed on cotton knit fabric. Two natural dyes from natural resources leaves Jujube leaves (JL) and Eucalyptus bark (EB) were extracted in an aqueous medium. A printing paste was produced using different proportions of two bio‐mordants. For an eco‐friendly printing process, tamarind seeds, and Indian gooseberries were used that have been extracted using a Soxhlet apparatus at 80°C for 8 h. All but a handful of samples using natural binders showed outstanding fastness in the printed sample which was graded 4 or 5. The development of the dye‐fiber bond was indicated by the presence of an intense covalent bond between the dye and fiber molecules as indicated by FTIR. The CMC lab data and K/S value of the printed samples were also obtained satisfactorily with maximum RFL value 77.319 and K/s value 1.659. This method not only lessens the environmental impact of the sector but also supports a better and more ecologically sensitive manufacturing technique. Moreover, sustainable apparel, household textiles, technical fabrics, and environmentally friendly packaging can all benefit from eco‐friendly printing using bio‐colorants and bio‐crosslinkers. Highlights Eco‐friendly printing on cotton using jujube and eucalyptus dyes reduces environmental harm. Bio‐mordants from tamarind seeds and gooseberry effectively replace harmful metal‐based mordants. Printed samples show excellent fastness ratings of 4–5, proving the quality of eco‐friendly printing. FTIR analysis confirms strong covalent bonds between dye and fiber molecules. This method supports sustainability by using renewable, biodegradable resources in textile production.